Manufacturing method of block body for dental prosthesis, manufacturing method of dental prosthesis
The method enhances the machinability of dental prosthesis block bodies by converting the main crystalline phase to lithium disilicate, addressing the challenge of efficient and defect-free production of dental prosthetics.
Patent Information
- Application Number
- JP2023010814
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-29
- Filing Date
- 2023-01-27
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2039-12-20
AI Technical Summary
Existing methods for manufacturing dental prosthesis block bodies struggle with achieving excellent machinability, which is crucial for rapid and defect-free production of dental prosthetics.
A method involving the exposure of a glass blank to an atmosphere above the production temperature of lithium disilicate crystals, followed by heating to convert the main crystalline phase to lithium disilicate, enhancing the machinability of the block body.
The method results in a block body for dental prosthetics with improved machinability, allowing for efficient cutting and grinding without defects, while maintaining the strength and aesthetic properties similar to natural teeth.
Smart Images

Figure 0007665663000002 
Figure 0007665663000003 
Figure 0007665663000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for manufacturing a block body for a dental prosthesis, and a method for manufacturing a dental prosthesis. [Background technology]
[0002] With the recent development of CAD / CAM (Computer Aided Design / Computer Aided Manufacturing) technology, the shape of the designed dental prosthesis can be converted into a specified format and handled as digital data, and this data can be sent to a processing device, which then automatically performs machining such as cutting and grinding based on the data to produce the dental prosthesis. This makes it possible to provide dental prostheses quickly.
[0003] Such dental prostheses are required to have the basic functions of a dental prosthesis, such as strength, hardness, and chemical durability against the oral environment, as well as aesthetics (color and texture) similar to natural teeth. In addition, dental prostheses have complex irregularities, and it is also important to machine complex shapes in a short time without causing defects such as chipping, etc. By using a material that can be machined in such a short time, dental prostheses can be manufactured more quickly.
[0004] Patent Document 1 discloses a dental prosthetic material containing specific components, which aims to improve the above-mentioned basic functions and machinability. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. WO2016 / 031399 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present disclosure is to provide a method for producing a block body for a dental prosthesis that has excellent machinability. [Means for solving the problem]
[0007] One aspect of the present disclosure is a method for producing a block body prior to machining for a dental prosthesis, comprising a step of heating a glass blank at a temperature below the formation temperature of lithium metasilicate crystals in an atmosphere at or above the formation temperature of lithium disilicate crystals and below the melting point so that the predominant crystal phase becomes lithium disilicate. Effect of the Invention
[0008] According to the present disclosure, a dental prosthesis block body with excellent machinability can be obtained. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a perspective view of the appearance of a dental prosthesis block body 10. FIG. [Diagram 2] FIG. 2 shows an enlarged view of a portion of the cut surface so that the crystals can be seen. [Diagram 3] FIG. 3 is a diagram for explaining a method for measuring the ratio. [Figure 4] FIG. 4 is another diagram illustrating the method of measuring the ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Specific examples of the embodiment will be described below, but the present invention is not limited to these examples.
[0011] First, a dental prosthesis block body produced by one embodiment of the manufacturing method for a dental prosthesis block body will be described. This dental prosthesis block body (hereinafter sometimes referred to as "block body") is prismatic, cylindrical, or plate-shaped (disk-shaped), and is deformed or cut out by machining such as cutting or grinding to produce a dental prosthesis. Among these, when producing a dental prosthesis by cutting, a prismatic or plate-shaped (disk-shaped) shape can be used. Prismatic block bodies are often used mainly to cut out a single dental prosthesis, and plate-shaped block bodies are sometimes used to cut out multiple dental prostheses from one block body.
[0012] Fig. 1 shows an external perspective view of a block body 10, which is a rectangular pillar. In the case of a rectangular pillar, the width W, depth D, and height H can each be in the range of 10 mm to 35 mm. On the other hand, in the case of a plate-shaped block body, the thickness can be configured to be in the range of 10 mm to 35 mm. This results in a block body that is easy to machine into dental prostheses.
[0013] To prepare the block according to this embodiment, the material can be composed of the following components: SiO2 is 60 mass% or more and 80 mass% or less, Li2O: 10% by mass or more and 20% by mass or less; Al2O3 is 3 mass% or more and 15 mass% or less.
[0014] The above components are as follows: If the SiO2 content is less than 60 mass% or exceeds 80 mass%, it becomes difficult to obtain a homogeneous block body, and the SiO2 content is more preferably 65 mass% or more and 75 mass% or less. If the Li2O content is less than 10 mass% or exceeds 20 mass%, it becomes difficult to obtain a homogeneous block body, and machinability tends to decrease. The Li2O content is more preferably 12 mass% or more and 18 mass% or less. If the content of Al2O3 is less than 3 mass%, lithium disilicate is precipitated as the main crystalline phase, but machinability tends to decrease. On the other hand, if the content of Al2O3 exceeds 15 mass%, the main crystalline phase is no longer lithium disilicate, and strength tends to decrease. More preferably, the content is 3 mass% or more and 7 mass% or less.
[0015] Furthermore, the dental prosthesis block may contain the following components in addition to the above components. However, as can be seen from the fact that the components shown here include 0% by mass, it is not necessary that any of the components be included, and any of them may be included.
[0016] The components for adjusting the melting temperature can be contained in an amount of 0% by mass or more and 15% by mass or less. This makes it possible to make the melting temperature appropriate in the manufacturing process described below. Although each of them may be contained in an amount of more than 15% by mass, the improvement in effect is limited. Specific examples of materials for the components for adjusting the melting temperature (melting temperature adjusting materials) include oxides of Na, K, Ca, Sr, Ba, Mg, Rb, Cs, Fr, Be, and Ra. More preferable are as follows. Na2O: 2.8% by mass or less K2O: 10% by mass or less CaO: 3% by mass or less SrO: 10% by mass or less BaO: 10% by mass or less MgO: 3% by mass or less Rb2O: 2.8% by mass or less Cs2O: 2.8% by mass or less Fr2O: 2.8% by mass or less BeO: 3% by mass or less RaO: 10% by mass or less
[0017] In addition, the components for forming the crystal nuclei can be contained in a range of 0% by mass to 10% by mass in total. This allows the nuclei for forming lithium disilicate crystals to be generated efficiently. However, even if more of the compounds are contained, the improvement in effect is limited, so the content is set to 10% by mass or less. Here, examples of compounds that function as materials (crystal nuclei forming materials) for the components for forming the crystal nuclei include oxides of Zr, P, and Ti (ZrO2, P2O5, TiO2). In this case, it is preferable that at least one selected from ZrO2, P2O5, and TiO2 is contained, and the total amount is 0% by mass to 10% by mass.
[0018] The material for the block may further contain a known coloring agent for enhancing aesthetics, such as at least one selected from V2O5, CeO2, Er2O3, MnO, Fe2O3, and Tb4O7.
[0019] Next, a method for producing a dental prosthesis will be described. This method includes a method for producing a block for a dental prosthesis. The method includes a melting step, a glass blank producing step, a heat treatment step, and a processing step.
[0020] In the melting step, the above-described components are melted at 1100°C to 1600°C. This makes it possible to obtain molten glass for a dental prosthesis block. This melting is preferably carried out for several hours in order to obtain sufficiently uniform properties.
[0021] The glass blank preparation process is a process for obtaining a glass blank having a shape similar to that of a dental prosthesis block. The molten glass obtained in the melting process is poured into a mold and cooled to a temperature below the temperature at which lithium metasilicate crystals form, preferably 400°C or less, more preferably 100°C or less, and even more preferably room temperature, to obtain a glass blank. The cooling is performed by slowly changing the temperature to prevent deterioration or cracking of the material.
[0022] The heat treatment step is a step of heating the glass blank obtained in the glass blank preparation step at a temperature equal to or higher than the formation temperature and lower than the melting point of lithium disilicate crystals, more preferably at a temperature within the range of 750°C or higher and 900°C or lower. In this step, rapid heating is preferable, so the glass blank, which has been cooled in the glass blank manufacturing step to a temperature lower than the formation temperature of lithium metasilicate crystals, preferably 400°C or lower, more preferably 100°C or lower, and even more preferably room temperature, is heated by being placed in a heating device such as a furnace to expose it to an atmosphere ranging from the formation temperature of lithium disilicate crystals to the melting point, more preferably 750°C to 900°C. The heating time is until the main crystal phase in the glass blank becomes lithium disilicate. Therefore, although it is not limited, it can be 20 minutes or more. Although the upper limit of the time is not particularly limited, it can be 6 hours or less. If the temperature is lower than the temperature at which lithium disilicate crystals form, there is a risk that a lithium disilicate blank having a lithium disilicate as the main crystalline phase cannot be obtained, whereas if the temperature is higher than the melting point of lithium disilicate crystals, there is a risk that the material will soften. After this rapid heating, the heating is stopped and the block is cooled to room temperature to obtain a dental prosthesis block having a main crystal phase of lithium disilicate. This cooling is preferably performed in a furnace by slow temperature change during natural cooling in the furnace. The term "main crystalline phase" as used herein means the crystalline phase having the largest proportion of crystals precipitated among the crystalline phases observed by analysis using an X-ray diffraction device.
[0023] In the heat treatment step, as described above, it is necessary to rapidly heat the material to within a predetermined temperature range. However, as long as the temperature is within the predetermined range, it is not necessary to maintain the material at a constant temperature, and the temperature may change.
[0024] The processing step is a step of machining the obtained dental prosthesis block into the shape of the dental prosthesis. The machining method is not particularly limited, but examples thereof include cutting and grinding. In this way, the dental prosthesis can be obtained.
[0025] This processing can be carried out under conditions with good productivity. In other words, until now, blocks for dental prostheses in which lithium disilicate is the main crystal phase have been difficult to machine efficiently because of their poor machinability. Therefore, it was necessary to prepare an easy-to-machine block that does not have lithium disilicate as the main crystal phase (for example, a block in which lithium metasilicate is the main crystal phase), machine it, and then heat-treat it after machining to change the main crystal phase to lithium disilicate, thereby later undergoing a process to increase the strength. In contrast, according to the present embodiment, even if the block body has a main crystalline phase of lithium disilicate, it can be cut or ground under conditions equal to or higher than those for a block body having a main crystalline phase of lithium metasilicate, which is easier to process. Furthermore, since no heat treatment is required after processing, the shape does not change and the machining accuracy is maintained, making it possible to make a dental prosthesis.
[0026] The block body produced by the manufacturing method of this embodiment has the following structure. Figure 2 shows an enlarged view of a part of a cross section of the block body 10 cut along the dotted line indicated by the symbol A1 in Figure 1. This view is an enlarged view with a field of view of 5 μm vertically (widthwise) and 5 μm horizontally (depthwise). Such a view can be obtained by a scanning electron microscope (SEM) image.
[0027] As described above, the main crystal phase of the block 10 is lithium disilicate.
[0028] In the block body 10, the total area of crystals having a length of 0.5 μm or more among the crystals appearing in the field of view shown in Fig. 2 is preferably 21% or less relative to the area of the field of view (5 μm × 5 μm) shown in Fig. 2, but it does not necessarily have to be 21% or less, and it is sufficient if the manufacturing method of this embodiment can reduce this ratio compared to conventional manufacturing methods. The ratio is preferably 10% or less, and more preferably 1% or less. Among the crystals that appear, the crystals having a length of 0.5 μm or more to be extracted may be limited to only crystals due to lithium disilicate. As a result, even if the block body has a main crystal phase of lithium disilicate, it can be cut or ground under conditions equal to or better than those for processing a conventional block body that is easy to process (for example, a block body whose main crystal phase is lithium metasilicate.) And, because this does not require heat treatment after processing, which is required for a block body whose main crystal phase is lithium metasilicate, for example, the shape does not change and the machining accuracy is maintained, making it possible to make a dental prosthesis.
[0029] Such a ratio is obtained as follows: Taking the block body 10 shown in Fig. 1 as an example, three cut surfaces are obtained in the largest direction (height direction in the example of Fig. 1), at the center A1, two end portions A2 located 10% from the end face of the total height H, and end portion A3. Of the three cut surfaces, the cut surface at the center A1 is shown in Fig. 3. Then, in the cut surfaces at the center A1, end A2, and end A3, scanning electron microscope images are obtained with a field of view of 5 μm×5 μm as shown in FIG. 2 for the center B1 shown by the dotted line, the two end B2 adjacent to the center B1 in the width W direction and located 10% from the end of the total width W, and the two end B3 adjacent to the center B1 in the depth D direction and located 10% from the end of the total depth D. Therefore, five images are obtained per cut surface, for a total of 15 images. Examples of the obtained images are shown in the upper part of FIG. 4.
[0030] Next, for each image, as shown in the bottom of Figure 4, crystals that are 0.5 μm or longer in length (the filled-in areas in the bottom of Figure 4) are extracted, and the sum S of the crystal areas is calculated. Next, the sum S of the areas is divided by the field of view area S0 (5 μm × 5 μm) of the image to express it as a percentage, and an individual ratio is obtained for each image. Thus, a total of 15 individual ratios are obtained. Then, the average of these individual ratios is calculated and used as the ratio.
[0031] Here, it is preferable that no voids are found in the dental prosthesis block. However, since the effect of some voids is considered to be small, it is preferable that the area occupied by voids is 2% or less on average in the observation range of 60 μm in length (width direction) × 60 μm in width (depth direction) at the 15 points where the above ratio was measured. Furthermore, it is preferable that no particulate matter of the coloring material is visible in a micrograph at a magnification of 200 times at the 15 points where the above ratio is measured. These voids and particulate matter may create an interface with the base material and affect machinability, and the presence of particulate matter in the coloring material may cause uneven coloring of dental prostheses. Such a dental prosthesis block can be reliably realized by molding the material by melting it as described above, rather than by powder molding.
[0032] The dental prosthesis blocks described above, and the dental prostheses manufactured from them, can provide the basic functions of a dental prosthesis, such as strength, hardness, and chemical resistance to the oral environment, as well as the same aesthetics (color and texture) as natural teeth. In addition, the machinability has been improved, and although it has the strength to not require heat treatment after processing, it can be machined without defects under processing conditions that are equal to or higher than those of conventional ceramic dental prosthesis blocks for cutting. EXAMPLES
[0033] In Examples 1 to 7 and Comparative Examples 1 to 6, the components and the heat treatment temperature were changed to prepare blocks by the melt molding method described above, and dental prostheses were fabricated by cutting to evaluate the machinability of the blocks. The block body is a rectangular parallelepiped with a width W of 14 mm, a depth D of 12 mm, and a height H of 18 mm.
[0034] The blocks according to Examples 1 to 7, Comparative Example 5, and Comparative Example 6 were prepared by rapid heating treatment as follows. For each example, the materials shown in Table 1 were mixed in the appropriate ratio and melted at 1300°C for 3 hours to obtain molten glass (melting process). The obtained molten glass was then poured into a mold and cooled to room temperature to obtain a glass blank (glass blank preparation process). The glass blank was then placed in a furnace preheated to the heat treatment temperature shown in Table 1 and maintained at the same heat treatment temperature for 30 minutes (heat treatment by rapid heating). It was then gradually cooled to room temperature (cooling process) to obtain a block body.
[0035] On the other hand, the blocks according to Comparative Examples 1 to 4 were prepared by a conventional heat treatment as follows. For each example, the materials shown in Table 1 were mixed in the appropriate ratio and melted at 1300°C for 3 hours to obtain molten glass (melting process). The obtained molten glass was then poured into a mold and cooled to room temperature to obtain a glass blank (glass blank preparation process). The obtained glass blank was then heated and maintained at 650°C for 60 minutes, and then heated to 850°C and maintained there for 10 minutes (heat treatment by conventional heating). It was then gradually cooled to room temperature (cooling process) to obtain a block body.
[0036] The content of each component is shown in mass% in Table 1. As can be seen from Table 1, Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, Example 3 and Comparative Example 3, and Example 4 and Comparative Example 4 have the same components except for the coloring agent. Table 1 also shows the type of heat treatment, the heat treatment temperature in the case of rapid heating, the type of main crystal phase of the obtained block body ("LDS" stands for lithium disilicate, "LS" stands for lithium metasilicate), the percentage of crystals with a length of 0.5 μm or more obtained by the above-described method, and the machinability. Note that the blanks in the component columns in Table 1 represent 0 mass%.
[0037] The main crystals were measured using an X-ray diffractometer (Empyrean (registered trademark); manufactured by Spectris Corporation), and as a result of quantitative analysis by the Rietveld method, the main crystals were determined to be the crystal phase with the highest crystal precipitation rate among the observed crystal phases.
[0038] The "ratio" refers to the ratio of crystals having a length of 0.5 μm or more, and is the area ratio (%) obtained by the method described above.
[0039] For "machinability," two types of conventional block bodies for machining were prepared as Reference 1 and Reference 2. The blocks are as follows: (Reference 1) A block material with lithium metasilicate as the main crystal phase, containing 72.3 mass% SiO2, 15.0 mass% Li2O, and 1.6 mass% Al2O3. (Reference 2) A block containing approximately equal amounts of lithium metasilicate crystal phase and lithium disilicate crystal phase, containing 56.3% by mass of SiO2, 14.7% by mass of Li2O, and 2.1% by mass of Al2O3. For the Examples and Comparative Examples, the machining time, tool wear, and chipping level of the block bodies of Reference 1 and Reference 2 when machined with a ceramic processing machine (CEREC (registered trademark) MC XL; manufactured by Sirona Dental Systems, Inc.) were evaluated. Those that were better than the block bodies of Reference 1 and Reference 2 in terms of machining time, tool wear, and chipping were evaluated as "good," and those that were less than the same as the block bodies of Reference 1 and Reference 2 in terms of machining time, tool wear, and chipping were evaluated as "poor."
[0040] [Table 1]
[0041] As can be seen from Table 1, the dental prosthesis block of the example has good machinability, even though the main crystal phase is lithium disilicate. Also, the "ratio" in the example was kept lower than that in the comparative example. It can also be seen that, although the components other than the coloring material are the same between Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, Example 3 and Comparative Example 3, and Example 4 and Comparative Example 4, the machinability and ratio are significantly different due to the different manufacturing processes. Comparative Example 5 could not obtain lithium disilicate as the main crystalline phase, and Comparative Example 6 experienced softening. All the blocks of the examples and the comparative examples had the necessary strength, and also satisfied the above-mentioned preferable conditions regarding voids and granular matter. [Explanation of symbols]
[0042] 10 Dental prosthetic blocks
Claims
1. 1. A method for producing a block body prior to machining for a dental prosthesis, comprising the steps of: The method includes a step of exposing a glass blank having a temperature of 400° C. or less to an atmosphere having a temperature of 800° C. or more and a temperature of 900° C. or less without preheating the glass blank once so that the main crystalline phase becomes lithium disilicate, the heating step is carried out so that, when a part of the cut surface of the block is observed in an enlarged field of view, the ratio of the sum of the areas occupied by crystals having a length of 0.5 μm or more in all crystals present in the enlarged field of view to the area of the enlarged field of view is 21% or less; A method for manufacturing a block body for a dental prosthesis.
2. 1. A method for producing a dental prosthesis, comprising the steps of: A process for producing a block body includes a step of exposing a glass blank having a temperature of 400° C. or less to an atmosphere having a temperature of 800° C. or more and a temperature of 900° C. or less without preheating the glass blank once so that the main crystal phase becomes lithium disilicate, the heating step is carried out such that, when a portion of a cut surface of the block is observed in an enlarged field of view, the ratio of the sum of areas occupied by crystals having a length of 0.5 μm or more in all crystals present in the enlarged field of view to the area of the enlarged field of view is 21% or less; After the heating step, the block body is cut without being subjected to a heat treatment, and after the cutting step, no heat treatment is performed. A method for manufacturing dental prostheses.
Citation Information
Patent Citations
Lithium disilicate glass ceramic, method for producing the same, and use
JP2013515659A
Dental restorative materials, methods for manufacturing the same, and glass ceramics
JP2014520061A
Dental crystallized glass block with an upper structure connected thereto and method for producing the same
JP2017531607A
Manufacturing method of crystallized glass capable of adjusting processability or light transmissivity by change of heat treatment temperature
JP2018145084A
Lithium silicate low temperature quartz glass ceramic
JP2018526317A